Benzoylation of polyphenylene oxide: characterization and gas permeability investigations - Bhole, Yogesh S.; Kharul, Ulhas K.; Somani, S. P.; Kumbharkar, S. C. (European Polymer Journal, 2005)
Benzoylation of polyphenylene oxide (PPO) was carried out with aromatic acid chlorides bearing specific groups at para-position (H methyl, Br, Cl and nitro), which differ in their polarity and bulk. The reaction conditions were optimized individually to get the high degree of substitution. These materials were characterized for thermal as well as other physical properties that are known to affect the gas permeation. In a series investigated, the nitrobenzoyl substitution on PPO resulted in the highest increase in glass transition temperature and the lowest thermal stability. An estimation of the packing density parameters-fractional free volume by density measurement and the d-spacing by X-ray diffraction analysis showed an increase in the packing density. The gas permeability was found to decrease in all the cases of benzoylation. The helium and oxygen based selectivities were increased, while CO2 based selectivities were decreased. The unusual trend observed in the gas permeation properties is explained on the basis of nature of substituent and the degree of substitution. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: benzoylation; Gas permeability; polyphenylene oxide; selectivity

Surface modification of polyacrylonitrile based ultrafiltration membrane - Lohokare, Harshada R.; Kumbharkar, S. C.; Bhole, Yogesh S.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2006)
Ultrafiltration membrane based on polyacrylonitrile prepared by phase inversion method using zinc chloride as an additive showed more than 90% rejection for BSA and 90-110 Im(-2) h(-1) water flux. The surface modification of this membrane was studied using ethanolamine, triethylamine, sodium hydroxide, and potassium hydroxide solutions. The effect of base treatment time and temperature on water flux and rejection was investigated. The membranes exhibited swelling by NaOH treatment followed by deswelling by HCl post-treatment, similar to pH responsive membranes. The treatment by organic as well as inorganic bases improved water flux with a slight lowering in BSA rejection by dead-end mode type treatment. A 230% increase in water flux was achieved by sodium hydroxide treatment in crossflow mode without a noticeable pore swelling by SEM. The contact angle of the modified membranes was decreased as compared to the unmodified one indicating appreciable surface modification. As the treatment time or temperature increased, the ESCA analysis showed increased population of Na-carboxylate groups. (c) 2006 Wiley Periodicals, Inc.
Keywords: BSA rejection; chemical treatment; polyacrylonitrile membrane; surface modification; Ultrafiltration

Variation in acid moiety of polybenzimidazoles: investigation of physico-chemical properties towards their applicability as proton exchange and gas separation membrane materials - Kumbharkar, S. C.; Islam, Md. Nazrul; Potrekar, R. A.; Kharul, Ulhas K. (Polymer, 2009)
A series of polybenzimidazoles (PBIs) were prepared from 3,3'-diaminobenzidine (DAB) and substituted aromatic dicarboxylic acids. Effects of added polarity, bulk and isomerism in the dicarboxylic acid moiety on the properties of formed aromatic polybenzimidazoles were investigated. Solution polycondensation procedure was optimized for individual case of PBI synthesis in order to obtain inherent viscosity of >= 1 dL/g. Analysis of physical properties, water uptake, acid doping (H(3)PO(4) and H(2)SO(4)) and gas permeability was performed. All these PBIs exhibited high thermal stability, good solvent solubility and amorphous nature. The uptake of H(3)PO(4) varied from 9 to 20.1 moles per repeat unit (mol/RU), H(2)SO(4) uptake varied from 3.39 to 3.81 mol/RU, while water uptake varied from 1.8 to 3.6 mol/RU of PBI. The dibromoterephthalic acid and tert-butylisophthalic acid based PBI showed the highest H(3)PO(4) uptake in the series, while tert-butylisophthalic acid based PBI exhibited the highest water uptake. Acid uptake was correlated with swelling of the PBI matrix, while density estimation of H(3)PO(4)-doped PBI by He gas expansion method could be correlated to the physical state of PBI. 5-tert-Butylisophthalic acid and 4,4'-(hexafluoroisopropylidene)bis(benzoic acid) based PBI exhibited higher H(2) and O(2) permeability than other PBIs. The ideal gas selectivity for O(2)/H(2) was considerably higher for most of the PBIs than conventional gas separation membrane materials. These analyses suggested that some of these PBIs have a potential to be used as a PEM or gas separation membrane material. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Gas permeability; Polybenzimidazole; Proton exchange membrane